Analisis Framing Pemberitaan Konflik di Tanah Melayu Rempang Pada Media Online Kompas.id - Quroatus Sholikha (Jurnal Ilmu Komunikasi, 2024)
This study aims to analyze how the online media Kompas.id frames its coverage of agrarian conflicts in Tanah Melayu Rempang, Batam, Riau Islands, which arose due to plans to develop the “Rempang Eco City” industrial area as part of the National Strategic Project (PSN). The research uses the framing analysis model developed by Zhongdang Pan and Gerald M. Kosicki, which includes four structures: syntactic, script, thematic, and rhetorical. In addition, the approach is reinforced by Max Horkheimer's critical theory to highlight the relationship between power, ideology, and domination in the construction of media reporting. The results of the study show that Kompas.id frames the Rempang conflict through a dominant narrative of national development and investment, in which local communities tend to be represented in a marginal position as parties who reject relocation. The syntactic and thematic structure of the news highlights the perspectives of the government and investors, while the historical aspects and identity of the indigenous Malay community appear limited and are not the main focus. From a critical theory perspective, this reporting reflects a form of instrumental rationality that places economic development above values of social justice and humanity.